A CMOS signal to noise measurement circuit for infrared sectored receivers - Alves, Luís Nero (2012)
This paper describes a circuit able to measure Signal to Noise ratios developed for Infrared applications. The Signal to Noise ratio is of major importance in IR Sectored Receivers because it provides the basis of selection or combining of signals coming from different optical sectors. This circuit estimates the ratio of the average optical signal sensed in the photo-detector and the average noise power present in the same photo-detector, with a 50dB output dynamic range.